Small molecule inhibitors of NOD2 signaling targeting the receptor-interacting protein kinase 2 - Dai, Bing. (2018)
Abstract: Receptor-interacting protein kinase 2 (RIPK2) mediates inflammatory signaling by the bacteria-sensing receptors Nucleotide-binding oligomerization domain-containing protein 1 and 2 (NOD1 and NOD2). Kinase inhibitors targeting RIPK2 are a proposed strategy to ameliorate NOD-mediated pathologies. Such as Crohn's diseases, Sarcoidosis, and inflammatory arthritis. For the further investigation of the RIPK2 function, finding or designing potent inhibitors is pretty important. Here we designed several inhibitors. To test their activity, we had three different methods, which can fully expose the activity of RIPK2 inhibitors. According to the HEK-BLUE assay, ADP-Glo assay as well as the Nano-BRET assay, we found several CSLP compounds show potent activity. Based on the residence time, we found there is no direct connection between the IC50 and the residence time. This project can provide strong date for further investigation of the function of the RIPK2 as well as the in-vivo experiment.; Thesis (M.S.)--Tufts University, 2018.; Submitted to the Dept. of Pharmacology and Drug Development.; Advisor: Alexei Degterev.; Committee: David Greenblatt.; Keyword: Pharmacology.